Urinary Tract Infections Caused by Staphylococcus saprophyticus and their antimicrobial sensitivity pattern in Young Adult Women (Bangladesh Journal of Medical Microbiology, 2011)
The present study was conducted to observe the antibiotic sensitivity pattern of isolated S. saprophyticus from urine samples of patients admitted in inpatient department or visited the out patient department of Sir Salimullah Medical College & Mitford Hospital (SSMC& MH) Dhaka from October 2002 to September 2003. Among the isolates, Esch.coli was the most predominant (82.61%) urinary pathogens followed by S. saprophyticus (7.01%). 93.10% S.saprophyticus was isolated from females of which highest (44.82%) rate of isolation was among female of 18- 45 years age group. Rate of isolation was also high (41.38%) among female of